The effectiveness of inspiratory muscle training in improving respiratory functional in COPD patients - Yodang, Y; Nuridah, N (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
The prevalence of Chronic Obstructive Pulmonary Disease (COPD) increases year by year worldwide and its related to mortality and decrease of quality of life. The majority of COPD patients complain about breathlessness and activity restrictions such as walking. In order to improve the status among COPD, implementing inspiratory muscle training was shown to benefit in reducing breathlessness. This study aims to determine the potential benefit of inspiratory muscle training in improving respiratory functional status by reducing breathlessness among COPD patients. This study applied a quasi-experimental approach with pre and post-test and control group design. There are 30 COPD patients who participate in this study and recruited by using purposive sampling methods and divided into two groups, intervention and control. Data collection using St George respiratory Questionnaire (SGRQ) and 6-Minute Walk Test (6MWT). Data analysis applied a T-paired test and the resulting p-value 0.001 for SGRQ, and 0.034 for 6MWT. This study finding concludes that inspiratory muscle training has potential benefit in improving respiratory functional status by decreasing breathlessness and improving tolerance in walking ability for 6 minutes in intervention groups.